2016
DOI: 10.3892/ol.2016.5474
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin, a natural lignan compound, induces G0/G1 cell cycle arrest and apoptosis in human glioma cells

Abstract: Abstract.The aim of the current study was to investigate the anticancer potential of arctigenin, a natural lignan compound, in malignant gliomas. The U87MG and T98G human glioma cell lines were treated with various concentrations of arctigenin for 48 h and the effects of arctigenin on the aggressive phenotypes of glioma cells were assessed. The results demonstrated that arctigenin dose-dependently inhibited the growth of U87MG and T98G cells, as determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…For the past several years, Arctiumlappa (burdock) and its active component Arctigenin have been reported to possess multiple bioactivities in vivo and in vitro (Holetz et al, 2002 ; Liu et al, 2012 ; Hwangbo et al, 2014 ; Wu et al, 2014 ). In addition, the potential targets and mechanisms of Arctigenin have been known, e.g., anti-inflammatory (via inhibition of nuclear factor kappa B (NF-κB) and inducible nitric oxide synthase (iNOS) (Liu et al, 2012 ; Hwangbo et al, 2014 ; Wu et al, 2014 ), immunomodulatory (via inhibiting nitric oxide, interlukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) production in macrophages) (Cho et al, 2004 ; Zhao et al, 2009 ; Zhu et al, 2013 ), amelioration of memory impairment (by suppressing microglia activation and decreasing IL-1β and TNF-α expression) (Lee et al, 2011 ; Zhu et al, 2013 ), anti-cancer (Kim et al, 2010 ; Sun et al, 2011 ; Lou et al, 2017 ; Maimaitili et al, 2017 ; Maxwell et al, 2017 ), and neuroprotection (Jang et al, 2002 ; Song J. et al, 2016 ). In addition, systematic pharmacological studies have been performed in multi-species (He et al, 2013 ; Gao et al, 2014 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the past several years, Arctiumlappa (burdock) and its active component Arctigenin have been reported to possess multiple bioactivities in vivo and in vitro (Holetz et al, 2002 ; Liu et al, 2012 ; Hwangbo et al, 2014 ; Wu et al, 2014 ). In addition, the potential targets and mechanisms of Arctigenin have been known, e.g., anti-inflammatory (via inhibition of nuclear factor kappa B (NF-κB) and inducible nitric oxide synthase (iNOS) (Liu et al, 2012 ; Hwangbo et al, 2014 ; Wu et al, 2014 ), immunomodulatory (via inhibiting nitric oxide, interlukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) production in macrophages) (Cho et al, 2004 ; Zhao et al, 2009 ; Zhu et al, 2013 ), amelioration of memory impairment (by suppressing microglia activation and decreasing IL-1β and TNF-α expression) (Lee et al, 2011 ; Zhu et al, 2013 ), anti-cancer (Kim et al, 2010 ; Sun et al, 2011 ; Lou et al, 2017 ; Maimaitili et al, 2017 ; Maxwell et al, 2017 ), and neuroprotection (Jang et al, 2002 ; Song J. et al, 2016 ). In addition, systematic pharmacological studies have been performed in multi-species (He et al, 2013 ; Gao et al, 2014 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… 26 We demonstrated that CXCL10 activated caspase-3 and caspase-8 in male germ cells. Notably, DEVD-fmk, a caspase-3 inhibitor, 27 protected germ cells from CXCL10-induced apoptosis. These observations suggested that CXCL10 induces germ cell apoptosis via the activation of caspase cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Arctigenin is a bioactive lignan isolated from the seeds of A. lappa and exerts anticancer activity through several different approaches (Awale et al, 2006;Gu, Scheuer, Feng, Menger, & Laschke, 2013;Kim et al, 2010). Arctigenin also has been reported could induce G0/G1 cell cycle arrest and/or apoptosis in different carcinoma cells (Jeong et al, 2011;Maimaitili et al, 2017). In recent years, several studies have shown that chemically synthesized arctigenin analogues exert strong anticarcinogenic activity (Cai et al, 2018;Lei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Arctigenin exhibits distinct biological activities, including antiviral (Dias et al, ; Hayashi, Narutaki, Nagaoka, Hayashi, & Uesato, ), neuroprotection (Song et al, ; Zhu et al, ), antidiabetic (Huang et al, ; Zeng et al, ), and anticancer (Chen et al, ; Huang et al, ; Hsieh et al, ; Jeong, Hong, Jeong, & Koo, ; Lei, Gan, Zhao, Yu, & Hu, ; Li, Liang, Tian, & Hu, ; Maimaitili et al, ; Wang, Solorzano, et al, ; Susanti et al, ). A growing body of literature documents that arctigenin can induce cell cycle arrests, apoptosis, autophagy, and antimetastasis in multiple types of cancer cells, including prostate (Wang, Solorzano, et al, ), breast (Feng et al, ; Hsieh et al, ; Lou, Zhu, Zhao, Zhu, & Zhao, ; Maxwell, Lee, Kim, & Nam, ), lung (Lei et al, ), liver (Susanti et al, ), gastric (Jeong et al, ), ovarian (Huang et al, ), colon cancer (Li et al, ), and glioma (Maimaitili et al, ). The anticancer efficacy of arctigenin in vivo also has been reported in human cancer cell xenograft model in athymic nude mice (Feng et al, ; Wang, Solorzano, et al, ).…”
Section: Introductionmentioning
confidence: 99%